(untitled) (Proceedings of the Global Public Health Conference, 2024)
From September 2019 to March 2023, UNICEF and the Government of Lesotho ran a three-year Integrated Nutrition and HIV/AIDS program across all districts. The main goal was to improve the health and nutrition of women and children, especially those affected by HIV/AIDS. The program aligned with global and regional directives, including the Sustainable Development Goals (SDGs) 2, 3, and 5, Africa’s Agenda 2063, and various national health strategies of Lesotho. The evaluation used a theory-driven methodology, leveraging the program’s Theory of Change (ToC) and Logical Framework (LogFrame) to assess key outcomes and outputs. A mixed-method approach included reviewing 20 essential documents and collecting primary qualitative and quantitative data at national, district, and community levels. Three districts and six communities were randomly selected for a comprehensive evaluation. The qualitative methods involved key informant interviews (KIIs) and focus group discussions (FGDs), supplemented by quantitative surveys of 48 households and 21 supervisors. Despite some challenges, there were significant positive changes in community health behaviours and nutritional outcomes, supported by community engagement, local governance, and behaviour change strategies. Male engagement notably contributed to achieving the program’s objectives. These findings provide a deeper understanding of community-centred program dynamics and offer important lessons for future health and nutrition interventions in marginalized settings. They also contribute valuable insights to both practical and policy discussions on integrated health programs.